1998
DOI: 10.1002/(sici)1096-8628(19980328)81:2<192::aid-ajmg12>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Association between novelty‐seeking and the dopamine D3 receptor gene in bipolar patients: A preliminary report

Abstract: Recent studies in healthy controls suggest an association between novelty-seeking (NS) and the dopamine D4 receptor (DRD4) gene. In this study, we further investigated the relationship between genes implicated in dopamine as well as serotonin neurotransmission and personality traits in bipolar (BP) disorder. Scores on the Tridimensional Personality Questionnaire were examined in 37 recovered Research Diagnostic Criteria-diagnosed BP patients genotyped for DRD3, DRD4, and serotonin 2A receptor (5HTR2a) polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
0
15
1
1
Order By: Relevance
“…An unexpected result was the correlation between novelty seeking and poor mental health. Prior studies have shown an association between novelty seeking and bipolar disorders, 34,35 but ours is the first to note an association with impulsive non-conformity. Further studies of the relationship between psychosis and affective disorders may be warranted.…”
Section: Discussioncontrasting
confidence: 46%
“…An unexpected result was the correlation between novelty seeking and poor mental health. Prior studies have shown an association between novelty seeking and bipolar disorders, 34,35 but ours is the first to note an association with impulsive non-conformity. Further studies of the relationship between psychosis and affective disorders may be warranted.…”
Section: Discussioncontrasting
confidence: 46%
“…38 DRD3 has also been linked to neuroticism and behavioral inhibition; however, this result has not been reproduced. 39,40 The other highly ranked SNPs for Agreeableness included rs11219218 (P ¼ 1.6 Â 10 À5 ), which is located 5 kb upstream of SCN3B and is responsible for generating and propagating action potentials in neurons and muscle. We also identified rs11219218 as being significantly associated with this trait (P ¼ 0.02); however, the GWA study showed an opposite trend.…”
Section: Agreeablenessmentioning
confidence: 99%
“…DRD3 has been implicated by association studies as a possible candidate gene for a number of neuropsychiatric disorders including schizophrenia, 2 alcoholism, 16,17 cocaine abuse, 18 bipolar illness, 19,20 Tourette syndrome, 21 opiate dependence, 22 novelty seeking, 23 anorexia nervosa, 24 Parkinson's disease 25 and others. In most cases the results have been inconclusive, partly due to small subject numbers.…”
Section: Discussionmentioning
confidence: 99%